KADAR PROTEIN DAN TEKSTUR PADA TEMPE KORO BENGUK DENGAN SUBSTITUSI KEDELAI HITAM - Yuni Safaratul Amanah; Yunan Kholifatuddin Sya’di; Erma Handarsari (Jurnal Pangan dan Gizi, 2019)
Tempe of koro benguk is a tempe made from raw koro benguk which has a fairly complete nutritional content. Black soybeanis local bean that have high protein content. The aim of this study was to describe the protein content  and texture from tempe of koro benguk substituted with black soybeans.This type of research is experimental design approach presented in descriptive form. Preparation of dumplings of koro tempe substituted with black soybean. Tthere were 5 treatments, each treatment was tested for protein levels and texture measurements 3 times. Measuring protein levels using the micro kjeldahl method and texture using the Texture Analyzer tool. The results of the study showed that the addition of black soybean to tempe of koro benguk gradually increased the protein content. The highest protein content is found in the formulation 20:80 which is equal to 17.84%. the more the addition of black soybean to the curry tempe, the texture of the hardness level in tempe is lower (soft), namely in the formulation of 20:80 which is worth 1.53 mm